P.S. Dijkstra – a Dutch Reformed missionary architect and his works in the Netherlands (Bulletin KNOB, 2023)
Pieter Simon Dijkstra (1884-1968) is regarded as a noted Protestant church designer in South Africa, but his contribution to the built environment in the Netherlands is much less well known. His life and career in the country of his birth are of interest because they are closely aligned with the religious turbulence of the period, in which the anti-revolutionary clergyman-politician Abraham Kuyper played a prominent role. The building of new Reformed churches and schools was a direct expression of the zealous determination to spread the ‘true faith’. The architecture of the new Reformed churches was often modest and restrained, influenced by Kuyper’s view that the church space should serve the ‘gathering of the faithful’ and be arranged in such a way that congregants could see and hear one other and the minister. Dijkstra, born to a clergyman father with a missionary zeal, delivered various designs in this Reformed context.Although Dijkstra grew up and trained in the northern Netherlands, Zeeland became  his main area of operation. In 1908, after time spent working in Groningen (Spijk) and Germany, Dijkstra settled in Vlissingen (Flushing) where he set up his own architectural practice. At the time Vlissingen was an internationally oriented city undergoing a radical transformation under the direction of the liberal alderman of public works, J.G. van Niftrik jr. (1889-1924). Dijkstra designed two new hall-type Reformed churches: one in Geersdijk (1910) and the Eben Haëzer church in Vlissingen (1910). There followed a remarkable inter-denominational collaboration after the English Presbyterian community’s place of worship in the St Jacob’s Church was destroyed by fire in 1911. After Dijkstra’s initial design for a simple hall church was rejected, the authoritative Catholic architect Pierre Cuypers (1827-1921) was commissioned to provide a sketch design for a small yet monumental building. Cuypers’ design for a neogothic church based on an octagonal plan was further elaborated by Dijkstra. The church was inaugurated in 1914.This unique project was followed by the Vlaswiek Reformed Church in Bovensmilde (Drenthe, 1915) and the Reformed Church in Kamperland (Noord-Beveland, 1923). The design for this robust church with corner tower and amphitheatre arrangement is in line with Kuyper’s views and foreshadows Dijkstra’s later church designs in South Africa.Dijkstra designed school buildings for the various Reformed communities in and around Vlissingen (in Koudekerke and Arnemuiden) and social housing estates, including three for the Protestant-Christian housing association Gemeenschappelijk Belang (Common Interest), partly in collaboration with P.J. Hamers (1882-1966). Among his commissions for retail spaces is the striking expressionist radio shop he designed for H.J. van der Meer en Zonen (1923 and 1926), still extant. In 1927, all out of the blue, Dijkstra decided to emigrate with his family to South Africa, where he continued to develop as a Reformed church architect. This article not only provides an assessment of his Dutch oeuvre as a prefiguration of his South African work, but it also positions him as an interesting architect within the Dutch context of his day, characterized as it was by verzuiling (lit. ‘pillarization’, a form of compartmentalization along socio-political or religious lines).